2004
DOI: 10.1038/sj.onc.1207547
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase III transcription and cancer

Abstract: RNA polymerase (pol) III synthesizes a range of essential products, including tRNA, 5S rRNA and 7SL RNA, which are required for protein synthesis and trafficking. High rates of pol III transcription are necessary for cells to sustain growth. A wide range of transformed and tumour cell types have been shown to express elevated levels of pol III products. This review will summarize what is known about the mechanisms responsible for this deregulation. Some transforming agents have been shown to stimulate expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
192
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(201 citation statements)
references
References 121 publications
2
192
0
Order By: Relevance
“…Indeed, Pol III transcription is, for example, elevated in cancer cells, and is globally diminished under certain conditions such as nutrient deprivation or other kinds of stress (for reviews, see White 2004;Goodfellow and White 2007;Gjidoda and Henry 2013). In yeast, a global Pol III transcription decrease upon nutrient deprivation is accompanied by a general decrease in Pol III occupancy at Pol III loci (Roberts et al 2003(Roberts et al , 2006Oficjalska-Pham et al 2006).…”
Section: A Spiking Methods To Normalize Chip-seq Experimentsmentioning
confidence: 99%
“…Indeed, Pol III transcription is, for example, elevated in cancer cells, and is globally diminished under certain conditions such as nutrient deprivation or other kinds of stress (for reviews, see White 2004;Goodfellow and White 2007;Gjidoda and Henry 2013). In yeast, a global Pol III transcription decrease upon nutrient deprivation is accompanied by a general decrease in Pol III occupancy at Pol III loci (Roberts et al 2003(Roberts et al , 2006Oficjalska-Pham et al 2006).…”
Section: A Spiking Methods To Normalize Chip-seq Experimentsmentioning
confidence: 99%
“…Studies have indicated that oncogenic proteins, such as c‐Myc, c‐Jun, c‐Fos, and Ras, increase Pol III gene transcription (Goodfellow et al ., 2006; Johnson et al ., 2008; Zhang et al ., 2011, 2013; Zhong and Johnson, 2007; Zhong and Johnson, 2009; Zhong et al ., 2011). In contrast, tumor suppressors, such as BRCA1, p53, PTEN, and pRB, decrease transcription of these genes (Johnson et al ., 2008; White, 2004; Woiwode et al ., 2008; Zhong et al ., 2015). The capacity of these oncogenic proteins and tumor suppressors to alter Pol III gene transcription results from their ability to regulate transcription factor III B (TFIIIB) complex activity.…”
Section: Introductionmentioning
confidence: 99%
“…The various chapters describe how the detailed knowledge of the molecular mechanisms and the signaling pathways which control mRNA translation and the protein synthetic machinery have identified steps potentially involved in tumorigenesis, in turn pointing at novel 'druggable targets' for cancer therapy (Bader and Vogt, 2004;Clemens, 2004;De Benedetti and Graff, 2004;Fingar and Blenis, 2004;Holland et al, 2004;Mamane et al, 2004;Perrotti and Calabretta, 2004;Rajasekhar and Holland, 2004;Rosenwald, 2004;Schmidt, 2004;Stoneley and Willis, 2004;White, 2004). Virtually all the reviews focus on the role that deregulated mRNA translation control may play in oncogenesis, describing the work performed in eukaryotic cells and mammalian systems.…”
Section: Introductionmentioning
confidence: 99%